Not All Antibiotic Use Practices in Food‐Animal Agriculture Afford the Same Risk. Issue 2 (1st March 2016) - Subbiah, Murugan; Mitchell, Shannon M.; Call, Douglas R.
Abstract : The World Health Organization has identified quinolones, third‐ and fourth‐generation cephalosporins, and macrolides as the most important antibiotics in human medicine. In the context of agricultural use of antibiotics, the principle zoonotic agents of concern are Salmonella enterica, Campylobacter spp., Escherichia coli, and Enterococcus spp. Antibiotic exposure provides a selective advantage to resistant strains of these bacteria relative to their susceptible conspecifics. This is a dose‐dependent process, and consequently antibiotic use practices that involve higher doses will exert greater and longer‐lasting selective pressure in favor of resistant bacterial populations and will therefore increase the probability of transmission to people and other animals. Oral administration has a greater impact on enteric flora with the exception of fluoroquinolone treatments, which appear to affect the enteric flora equally if administered orally or parenterally. The use of quinolones in agriculture deserves heightened scrutiny because of the ease with which these broad‐spectrum antibiotics favor spontaneously resistant bacteria in exposed populations. When present at sufficient concentrations, excreted antibiotics have the potential to selectively favor resistant bacteria in the environment and increase the probability of transmission to people and animals. The bioavailability of antibiotics varies greatly: some antibiotics remain active in soils (florfenicol, β‐lactams), whereas others may be rapidly sorbed and thus not bioavailable (tetracycline, macrolides, quinolones). When considering the risks of different antibiotic use practices in agriculture, it would be prudent to focus attention on practices that involve high doses, oral delivery, and residues of antibiotics that remain active in soils. Core Ideas: The use of antibiotics in agriculture is thought to contribute to antibiotic resistance worldwide. Risk assessment should focus on the largest potential contributors to antibiotic resistance. Antibiotic dose and administration practices are key variables. Excreted antibiotics may play an important role, but not all antibiotics remain active in soil. The use of quinolones in agriculture deserves special scrutiny.